Additional support to children with obstacles in development - Bogoevska, Natasha; Dimitrijoska, Suncica; Trbojevik, Svetlana (Ревија за социјална политика/Journal of Social Policy, 2017)
The system of social, health and educational protection of children with disabilities in the Republic of Macedonia experience ongoing changes. The main goals of the reforms are harmonization of the Macedonian legislation with international standards, as well as improvement of the position of the disabled person in society through social and labour inclusion. Besides the traditional forms of protection of disabled children, there are attempts for introduction of new measures and activities targeting disabled children which will enable a higher degree of social and health protection, social involvement, regular school attendance and better achievements in the educational process. The current situation shows that there is no integral legal text that fully regulates the rights of disabled persons. On a contrary, rights for disabled persons and children with impairments in the development are legally regulated in number of laws and bylaws. The conducted researches point out to certain weaknesses in the existing legal and institutional framework, as well as in the process of its implementation. There are several limitations even in the first phase of identification and assessment of children with impairment. Some of them are systematic and occur as a result of the different practices of the bodies responsible for the assessment of disabled children and in the exclusive use of the medical model of assessment. Some of the reasons for insufficient level of protection of disabled persons and their families are located in the inappropriate material assistance, lack of institutional structures such as local services for support. The society recognizes the need for in-depth reforms in the system of support of persons with disabilities. A number of activities, mainly supported by international organizations, are in the process of implementation and required sustainability through provision of state ownership. In that regard, by applying the measures of additional support for persons with disabilities the process is moving towards providing a holistic approach in overcoming of existing problems. The precondition for successful response to identified shortfalls is the development of a whole range of services in the local community delivered by multi-sectoral cooperation.